2021
DOI: 10.1038/s41598-021-98961-2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of hospitalization using artificial intelligence for urgent patients in the emergency department

Abstract: Timely assessment to accurately prioritize patients is crucial for emergency department (ED) management. Urgent (i.e., level-3, on a 5-level emergency severity index system) patients have become a challenge since under-triage and over-triage often occur. This study was aimed to develop a computational model by artificial intelligence (AI) methodologies to accurately predict urgent patient outcomes using data that are readily available in most ED triage systems. We retrospectively collected data from the ED of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…According to the South Korea 2021 Emergency Medical Statistical Yearbook, only 7.1% of patients visiting the emergency department had a high severity of KTAS 1 and 2, but 92.9% of patients had KTAS 3-5, it is becoming the main cause of emergency department overcrowding [6]. In particular, in the current triage system, classi cation accuracy is reduced owing to middle-level classi cation ambiguity, such as level 3 [48], and some patients classi ed as nonemergency patients face problems of undertriage and overtriage [49,50]. In addition, previous studies have shown that a triage system using an automated algorithm predicts hospitalization for ESI level 3-5 patients better than nurses do, suggesting the need for AI-based triage to increase the accuracy of classi cation by targeting level 3-5 patients [51].…”
Section: Discussionmentioning
confidence: 99%
“…According to the South Korea 2021 Emergency Medical Statistical Yearbook, only 7.1% of patients visiting the emergency department had a high severity of KTAS 1 and 2, but 92.9% of patients had KTAS 3-5, it is becoming the main cause of emergency department overcrowding [6]. In particular, in the current triage system, classi cation accuracy is reduced owing to middle-level classi cation ambiguity, such as level 3 [48], and some patients classi ed as nonemergency patients face problems of undertriage and overtriage [49,50]. In addition, previous studies have shown that a triage system using an automated algorithm predicts hospitalization for ESI level 3-5 patients better than nurses do, suggesting the need for AI-based triage to increase the accuracy of classi cation by targeting level 3-5 patients [51].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that early prediction of admission and discharge probabilities during the ED triage process could be utilized to enhance patient flow and contribute to more effective bed management. AI models were found to have the potential to streamline ED operations, mitigate challenges associated with ED crowding, as well as contribute to the efficient management of ED resources [23].…”
Section: Triage Efficiencymentioning
confidence: 99%
“…The combined model demonstrated a sensitivity of 58% in detecting NSICU admission with a false positive rate of 1:100 (99% specificity). Another study conducted using data from a tertiary teaching hospital in Taiwan focused on urgent level-3 patients and found that using an AI model achieved an AUROC of 0.8004 and accurately determined the necessity of hospitalization for patients requiring urgent attention [23].…”
Section: Predicting Hospital Admissionmentioning
confidence: 99%
See 1 more Smart Citation
“…With advances in AI, personalized predictions and prevention are possible ( 65 , 66 ). Up to now, multiple disease prediction models had been developed and improved to provide targeted and personalized health advice ( 67 70 ). Furthermore, AI has also greatly contributed to the development of the psychological counseling industry.…”
Section: The Application Of Artificial Intelligence In Public Healthmentioning
confidence: 99%